2008
DOI: 10.1002/bip.21017
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman difference between bombesin and its modified analogues on the colloidal and electrochemically roughen silver surfaces

Abstract: In this article, surface-enhanced Raman scattering (SERS) spectra of bombesin (BN) and its six modified analogues ([D-Phe(12)]BN, [Tyr(4)]BN, [Tyr(4),D-Phe(12)]BN, [D-Phe(12),Leu(14)]BN, [Leu(13)-(R)-Leu(14)]BN, and [Lys(3)]BN) on a colloidal silver surface are reported and compared with SERS spectra of these species immobilized onto an ellectrochemically roughen silver electrode. Changes in enhancement and wavenumber of proper bands upon adsorption on different silver surfaces are consistent with BN and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 62 publications
7
49
1
Order By: Relevance
“…For AgNPs, cysteine (36) and amine-bearing amino acids (37) contain the bond-forming residues. In addition, carboxyls (36,38,39) and aromatics (36)(37)(38)40) were also found to be involved. One study alone identified sulfhydryl, carboxyl, aromatic, and imino groups across a wide range of proteins as responsible for binding to AgNPs (41), suggesting binding may be controlled not by a single amino acid but by specific sequences of amino acids.…”
Section: Resultsmentioning
confidence: 96%
“…For AgNPs, cysteine (36) and amine-bearing amino acids (37) contain the bond-forming residues. In addition, carboxyls (36,38,39) and aromatics (36)(37)(38)40) were also found to be involved. One study alone identified sulfhydryl, carboxyl, aromatic, and imino groups across a wide range of proteins as responsible for binding to AgNPs (41), suggesting binding may be controlled not by a single amino acid but by specific sequences of amino acids.…”
Section: Resultsmentioning
confidence: 96%
“…41,43 Although in the case of these peptides adsorbed on the colloidal silver surface their -NH 2 group interacts with the silver nanoparticles. 42,44 …”
Section: Discussionmentioning
confidence: 98%
“…41,43 In each case, bands associated with Trp 8 dominated the SERS spectra, thus confirming previously obtained results. [41][42][43][44] Therefore, it may be deduced that this residue was involved in substrate binding to the Ag surface, although it occurred in a different manner for each peptide. In addition, the SERS spectra (see Figure 3) differed substantially from the corresponding FT-RS spectra (see Figure 2).…”
Section: Sers Studiesmentioning
confidence: 97%
“…[18,27,28] Weak |E| 2 is also accounted for by the small surface roughness (r of ∼12 nm) due to the ineffective surface plasmon energy radiation. [25,27,29] In contrast, the modified substrate with T MW of 200 s ( Fig. 1(b)) exhibits ∼14- fold improvements in |E| 2 compared to the as-grown substrates (maximum intensity counts of 47 763 in Fig.…”
Section: Discussionmentioning
confidence: 99%